Ebola Virus Disease (Evd) or Ebola Hemorrhagic Fever (Ehf) - N.Sriram (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Ebola virus disease (EVD), also known as Ebola haemorrhagic fever, is a severe, often fatal illness in humans. EVD outbreaks have a case fatality rate of up to 90%. EVD outbreaks occur primarily in remote villages in Central and West Africa, near tropical rainforests. The virus is transmitted to people from wild animals and spreads in the human population through human-to-human transmission. Fruit bats of the Pteropodidae family are considered to be the natural host of the Ebola virus. Severely ill patients require intensive supportive care. No licensed specific treatment or vaccine is available for use in people or animals.